Estudio de la actividad enzimática de la enzima comercial papaína a diferentes pH, temperatura y concentración de sustrato - Lombeida Fajardo, Abigail Alejandra (2025)
The objective of this research was to study the enzymatic activity of the commercial enzyme papain at different pH levels, temperatures, and substrate concentrations. This experimental study consisted of 180 g of casein and 96 g of commercial papain enzyme, divided into 2 g for each test. The independent variables manipulated were pH, temperature, and substrate concentration, while the dependent variable was enzymatic activity, measured by UV spectrophotometry according to changes applied to the experimental conditions. The results obtained at different pH levels showed that both the substrate and pH act independently, with minimal interaction observed between pH 6 and 7. At 65 °C, enzymatic activity progressively increased until reaching its maximum capacity. Subsequently, the influence of substrate concentration was evaluated under conditions of pH 7 and 50 °C, revealing higher oxygen consumption and faster reaction rates at concentrations of 18.75 mM and 20.83 mM. The Michaelis–Menten model accurately described the enzyme’s kinetic behavior, yielding a determination coefficient of R² = 0.9863, indicating a reliable model fit. The kinetic parameters obtained were Kₘ = 36.65 mM and Vmax = 0.015785 mmol/min, suggesting a low affinity of the enzyme for the substrate in its commercial form. These results provide insight into the optimal conditions for the efficient use of papain in industrial processes requiring protein degradation.